The Analysis of Slang Words in The “Straight Outta Compton” Movie Script - Marpaung, Ezekiel Benjamin Taffarel; Ayu Widiastuti, Ni Made; Ketut Mas Indrawati, Ni Luh (Research and Community Services Institutes of Udayana University, 2024)
This study aims at finding out and describing kinds of slang words found in the Straight Outta Compton movie script, especially those used by the main character as well as analyzing their meanings. This study contributes knowledge of slang language in use to listeners or audiences. The data were collected by reading the Straight Outta Compton movie script, and then listing the data that are taken from the dialogues done by the characters. In the findings of this research, there are two points that are answered based on the problems of the research. The first part is the types of slang words used in Straight Outta Compton movie script can be classified into Society slang, Cockney slang, and Public House slang. And the second part is the meaning of the slang words in the Straight Outta Compton movie script which the point is to explain the function of the word that indicates based on how those words are used in conversation. The slang words are in the form of nouns, verbs, and adjectives used in the sense of kindness and also in the sense of harshness.